Qualidade de vida de policiais penais do estado do Ceará - Siqueira, Cícero Mendes (2023)
Quality of life is conceptualized as "the individual's perception of their position in life in the context of the culture and value systems in which they live, and in relation to their goals, expectations, standards, and concerns." Work is important and has an influence on the motivation, satisfaction, and productivity of the worker. In the case of police work, it is characterized as a job with social and criminal risks due to the challenges imposed by dealing with criminality and the significant responsibility and social demand involved. Criminal police officers perform various activities, with the primary goal of inmate rehabilitation. In light of this, the objective of this study is to assess the quality of life and work quality of criminal police officers in the state of Ceará. This is a cross-sectional, quantitative, and correlational study. The study will follow the recommendations of the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) initiative. The research was conducted in prison units across all macro-regions of the state of Ceará. Data collection took place from June to August 2022 in the prison units identified by the stratified sample. The sample was estimated at 342 criminal police officers, but the total number of respondents was 344. The study investigated socio-economic and demographic data, health habits, overall quality of life ( WHOQOL-Bref ), and work quality of life (QWLQ-78-Bref). among the participants. In the quantitative analysis, the Statistical Package for the Social Sciences (SPSS) version 23.0 for Windows® was used for database construction and statistical treatment. This research project is part of the initiative titled "Promotion of health and quality of life in the penitentiary system of Ceará," which was submitted to the Ethics and Research Committee of the Federal University of Ceará and received favorable approval under the number 57107722.6.0000.5054. The study involved 344 participants, predominantly under 40 years old (66.3%), suggesting a young age distribution, with the majority identifying as non-white (70.6%). The participants were mostly male (77%), Catholics (54.7%), and married (54.7%). The average income was R$10,506.94, and 68% affirmed to be satisfied with it. Participants showed good overall quality of life (QOL: 62.83), with higher scores in Psychological and Social Relationships QOL. Positive perceptions were observed in Work Quality of Life (WQOL Total: 57.67). The personal dimension obtained the highest score (Personal WQOL: 65.73), and the Physical/Health, Psychological, and Professional dimensions also showed positive results, with scores of 55.33, 58.04, and 55.60, respectively. Statistically significant associations were observed in individual vulnerabilities such as age, marital status, city of residence, kids, and income satisfaction across different dimensions of QOL. In social vulnerabilities, such as comorbidities and lack of adequate physical activity, dissatisfaction with equipment, work schedule, and experience of workplace violence were associated with lower QOL and WQOL. Meanwhile, programmatic vulnerabilities such as the desire to resign the police force, engaging in extra paid activities, and experiencing violence showed significant associations with lower QOL and WQOL in various dimensions.